Troubleshooting on biogas production by using factorial analysis in sewage treatment plant (STP) - Mohd Faizan, Jamaluddin; Norazwina, Zainol; Nurul Shareena Aqmar, Mohd Sharifa (Elsevier, 2021)
The improvement on biogas production from anaerobic digestion system requires a meticulous analysis in troubleshooting especially in the case of meltdown or failure. The involvement of rapidly mutated bio-organism is a major setback to instantly trace and correct the faults in the system. Fractional factorial design was applied in this study to improve the process troubleshooting in STP. It was performed using five control parameters including pH (A), total solid (TS), feedstock recirculation (FR), inoculum percentage (IP) and hydraulic retention time (HRT) on the biogas production. The results demonstrate that pH (6.0), TS (4.0%), feedstock recirculation (4%), inoculum percentage (33%) and sludge retention time (14 days) produced the highest yield of biogas. Four significant effects for the process passed the Bonferroni limit, with two interaction effects between CD (FR and IP) and BE (TS and HRT) with 19.59% and 11.36% percentage contribution. A strict yet suitable amount of inoculum, time, and substrate was acquired in the high-efficiency process. The rest were the main factors of E: HRT with 15.27% and A: pH with 12.69% contribution demonstrates the importance of contact time between microbe and substrate, and the process environment. The outcome from the study proves that, the improvement of process troubleshooting using factorial analysis is highly beneficial and useful to sustain an efficient digestion system.